Critical Ethnographic Communication in Supporting Corporate DEI and CSR - Amrinagara, Muhammad Alfath Fiqhya; Ayuningtyas, Fitria (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
Social inequality in multicultural and hierarchical workplaces challenges companies in implementing Diversity, Equity, and Inclusion (DEI) and Corporate Social Responsibility (CSR) programs. This study uses a critical ethnographic approach as a transformative organizational communication strategy to uncover and address hidden social issues. Unlike top-down symbolic methods, critical ethnography amplifies marginalized voices such as women, people with disabilities, and ethnic minorities. Through qualitative descriptive analysis of literature and Unilever Indonesia’s case, the study finds that integrating ethnographic insights into DEI and CSR communication exposes structural bias, fosters inclusive narratives, and supports socially just policies. Companies applying this approach become more responsive to social crises and build stronger, sustainable community relations. Furthermore, two-way communication based on real experiences strengthens ESG value internalization, positioning critical ethnography not just as observation but as a strategic bridge between corporations and complex social realities.